2022
DOI: 10.1007/s10198-022-01478-2
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the cost-effectiveness of renal replacement therapies, and consequences for decision-making in the end-stage renal disease treatment pathway

Abstract: Objectives Comparative economic assessments of renal replacement therapies (RRT) are common and often used to inform national policy in the management of end-stage renal disease (ESRD). This study aimed to assess existing cost-effectiveness analyses of dialysis modalities and consider whether the methods applied and results obtained reflect the complexities of the real-world treatment pathway experienced by ESRD patients. Methods A systematic literature re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(126 reference statements)
0
8
0
Order By: Relevance
“…Renal replacement therapy (RRT), such as kidney transplantation, peritoneal dialysis and haemodialysis, is a lifesaving but costly treatment for ESRD patients [3]. While kidney transplantation is the optimal RRT, dialysis remains the feasible RRT for ESRD patients because of the shortage of kidneys and the medical ineligibility of some patients for transplation [4,5]. Haemodialysis is the predominant RRT option in Nigeria [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Renal replacement therapy (RRT), such as kidney transplantation, peritoneal dialysis and haemodialysis, is a lifesaving but costly treatment for ESRD patients [3]. While kidney transplantation is the optimal RRT, dialysis remains the feasible RRT for ESRD patients because of the shortage of kidneys and the medical ineligibility of some patients for transplation [4,5]. Haemodialysis is the predominant RRT option in Nigeria [2].…”
Section: Introductionmentioning
confidence: 99%
“…Most published studies on the cost-effectiveness of RRT have focused on high-income countries and compared alternative dialysis types or dialysis modalities with different intensities [1,3,4]. Many studies reported average cost-effectiveness ratios that are less useful for decisionmaking when moving between alternative modalities than incremental cost-effectiveness ratios (ICERs) [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 , 3 , 10 , 11 ] Authors of a recent systematic review suggested a more comprehensive cost-effectiveness approach that considers different renal replacement therapy (RRTs) along the patient pathway since switching between dialysis modalities is often essential. [ 11 ] According to expert opinion, [ 12 , 13 ] PD should ideally reach 30% to 45% of patients starting RRT. However, the use of PD is considerably low in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…[2,3] Similar to hemodialysis (HD), peritoneal dialysis (PD) is an effective technique for the treatment of ESKD, [4][5][6][7][8][9] but most economic evaluations indicate that it is more cost-effective. [2,3,10,11] Authors of a recent systematic review suggested a more comprehensive cost-effectiveness approach that considers different renal replacement therapy (RRTs) along the patient pathway since switching between dialysis modalities is often essential. [11] According to expert opinion, [12,13] PD should ideally reach 30% to 45% of patients starting RRT.…”
Section: Introductionmentioning
confidence: 99%